Diagnosis, prevention and control of urinary tract infections: a survey of routine practices in Belgian nursing homes - Latour, Katrien (J Infect Prev, 2020)
BACKGROUND: Urinary tract infections (UTIs) are one of the most frequently reported infections in older adults and the most common reason for antimicrobial prescribing in nursing homes (NHs). In this vulnerable population, both a good diagnosis and prevention of these infections are crucial as overuse of antibiotics can lead to a variety of negative consequences including the development of multidrug-resistant organisms. OBJECTIVE: To determine infection prevention and control (IPC) and diagnostic practices for UTIs in Belgian NHs. METHODS: Local staff members had to complete an institution-level questionnaire exploring the availability of IPC practices and resources and procedures for UTI surveillance, diagnosis, and urinary catheter and incontinence care. RESULTS: UTIs were the second most common infections in the 87 participating NHs (prevalence: 1.0%). Dipstick tests and urine cultures were routinely performed in 30.2% and 44.6% of the facilities, respectively. In non-catheterised residents, voided or midstream urine sampling was most frequently applied. Protocols/guidelines for urine sampling, urinary catheter care and incontinence care were available in 43.7%, 45.9% and 31.0% of the NHs, respectively. Indwelling catheters were uncommon (2.3% of the residents) and urinary retention (84.9%) and wound management (48.8%) were the most commonly reported indications. Only surveillance was found to significantly impact the UTI prevalence: 2.2% versus 0.8% in NHs with or without surveillance, respectively (P < 0.001). DISCUSSION: This survey identified key areas for improving the diagnosis and prevention of UTIs, such as education and training regarding the basics of urine collection and catheter care.